Zealastoa Quicke & Ward, gen. nov., a new basal cyclostome braconid wasp (Hymenoptera: Braconidae) from New Zealand. Issue 3 (3rd September 2020) - Quicke, Donald L J; Ward, Darren F; Belokobylskij, Sergey A; Butcher, Buntika A
Abstract: The Mesostoinae are an almost entirely Gondwanan subfamily of Braconidae, known from Australia, New Zealand and South America (extending into MesoAmerica). They are morphologically and biologically diverse and, together with Aphidiinae and Maxfischeriinae, are the sister group to all other extant cyclostome braconids. Here we describe and illustrate a new genus, Zealastoa Quicke & Ward, gen. nov., and three new species: Z. waitakerensis Quicke & Ward, sp. nov., Z. hirta Belokobylskij, Quicke & Ward, sp. nov., and Z. multiarticulata Belokobylskij, Quicke & Ward, sp. nov., all from New Zealand. Molecular phylogenetic analysis based on combined nuclear 28S rDNA D2‐D3 expansion region and the barcoding region of mitochondrial COI strongly support a monophyletic clade comprising the endemic New Zealand genera ( Doryctomorpha Ashmead, Metaspathius Brues, Rhyssaloides and Zealastoa gen. nov. ) as being the sister group to all other members of the subfamily.